Pengaruh Aplikasi Bacillus thuringiensis Terhadap Populasi Predator dan Parasitoid pada Sawi - Hendra Manyu; Akhmad Gazali; Jumar Jumar (Agroekotek View, 2018)
The purpose of this study was to investigate the effect of Bacillus thuringiensis on the predator and parasitoid populations of mustard greens and to identify species of predators and parasitoids in Bacillus thuringiensis treated sauce. This study used a single factor Randomized Block Design with 5 treatments and 4 replications. The treatment consists of a). Control (water) b). Bacillus thuringiensis solution (2cc / l water) c). Bacillus thuringiensis solution (4 cc / l water) d). Bacillus thuringiensis solution (6 cc / l water) e) Bacillus thuringiensis solution (8 cc / l water). The results showed that the administration of Bacillus thuringiensis did not affect the predation of trapped predator and parasitoid populations, and found 12 species of predators consisting of 3 ordo of Arachnida, Coleoptera, Orthoptera, and parasitoid species of 8 species from Hymenoptera ordo.